2007
DOI: 10.1111/j.1467-8578.2007.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of special schools for children with profound and multiple learning difficulties: is segregation always best?

Abstract: This paper presents an interpretivist, qualitative research project which intended to illuminate issues related to supporting 'inclusion' of children with profound and multiple learning difficulties in a special school for children with severe learning difficulties in the Southwest of England. The research found that, in spite of its reputation, the school struggled significantly to provide and appropriate learning experience for children with PMLD. The paper discusses the need for better staff training to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…Such findings are of concern because a lack of knowledge and preparedness on the part of teaching assistants affects the extent to which students with learning disabilities can access education in both special and mainstream environments (Abbott, McConkey & Dobbins, 2011), and limits their opportunities for inclusion. Indeed, Simmons and Bayliss (2007) demonstrated that teachers and teaching assistants who supported pupils with severe learning difficulties (SLD) failed to provide appropriate learning opportunities for students with profound and multiple learning disabilities (PMLD) who were included in their classrooms, because they did not understand the different pedagogical approach that was required.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings are of concern because a lack of knowledge and preparedness on the part of teaching assistants affects the extent to which students with learning disabilities can access education in both special and mainstream environments (Abbott, McConkey & Dobbins, 2011), and limits their opportunities for inclusion. Indeed, Simmons and Bayliss (2007) demonstrated that teachers and teaching assistants who supported pupils with severe learning difficulties (SLD) failed to provide appropriate learning opportunities for students with profound and multiple learning disabilities (PMLD) who were included in their classrooms, because they did not understand the different pedagogical approach that was required.…”
Section: Introductionmentioning
confidence: 99%
“…Mainstream provision: advantages and challenges Stevens (2005) argued that special schools for disabled people should be closed, and compared the concept to the racist ideas and institutions of the twentieth century. Additionally, contrary to the perspective that special schools are the most appropriate setting for children with PMLD, Simmons and Bayliss (2007) called for an appraisal of the view that special schools provide the best educational environment for such pupils. Their research, based on observations and interviews in a highly regarded special school in south-west England for children with SLD, concluded that because of a lack of staff knowledge and training it was inappropriate provision.…”
Section: Special Schools: Advantages and Challengesmentioning
confidence: 99%
“…The nature of (special) education for students with disabilities continues to come under question, particularly in the context of the inclusion debate (Australian Association of Special Education, 2010; Simmons & Bayliss, 2007;Slee, 2011;Smith, 2007). Intended outcomes and learning goals for students with MSID are often so individual and their post-school lives so different from those anticipated for most of their same-age peers (due to their lifelong dependence in all activities of daily living) it might be said that the nature of their education is in some ways fundamentally different from that of most other students (Lyons, 2003).…”
Section: Assessmentmentioning
confidence: 99%
“…Public special schools for students with intellectual disabilities, including some with MSID, were established. With tightening government regulations surrounding the provision of funding, the prevailing care paradigm eventually transformed to the education paradigm and a professional acceptance of the principle that all children were educatable took hold (Simmons & Bayliss, 2007). During the latter part of the 20th century, the disability studies movement found considerable traction in the public arena, whereas in education the discourses of mainstreaming and integration took precedence (Connor, Gabel, Gallagher, & Morton, 2008).…”
Section: Introductionmentioning
confidence: 99%